PMP Exam Cram, 5th Edition - Solomon, Michael 1963- (Pearson IT Certification, 2014)
The Publisher regrets that the CD/DVD content for this title cannot be made available Online> PMI's PMP certification is the world's leading project management credential: indispensable for everyone who intends to succeed in the field. PMI has recently revamped its foundational Project Management Body of Knowledge to incorporate new processes and an entirely new area of knowledge: Project Stakeholder Management. The new PMP exam reflects all these significant modifications. PMP Exam Cram, Fifth Edition offers condensed, focused preparation for every topic on this new exam, including all five new processes. It addresses the entire project lifecycle, including initiation, planning, execution, monitoring, control, closing, and more; and offers essential information about professional responsibility and other key topics. Like all Exam Cram books, PMP Exam Cram, Fifth Edition is carefully designed to help you study more efficiently, productively, and successfully. It brings together: Chapters that map directly to the exam objectives Comprehensive foundational learning on all topics covered on the exam Cram Saver quizzes to help you assess your knowledge in each section Concise topic review sections help you understand exactly what you'll need to know Exam Alerts help identify potential exam trouble spots An extensive collection of practice questions (including two full practice exams) Notes, tips, sidebars, cautions, test-taking strategies, and time-saving study tips The Cram Sheet tear-out card including tips, acronyms, and memory joggers not available anywhere else - perfect for last-minute study.
Online resource; Title from title page (viewed November 7, 2014)
Keywords: Project management -- Study guides -- Examinations; Gestion de projet; Examens; Guides de l'étudiant; Project management; Examinations; examination study guides; Study guides; Guides de l'étudiant